Типологія прецедентних імен у газетних заголовках - Sunko, Nataliia (Рута, 2021)
The article is devoted to the study and analysis of precedent names of three cultural spheres ("Bible", "Literature", "Mythology") in newspaper headlines. The subject of the study is a typology of precedent names in newspaper headlines. The object of it is newspaper headlines of modern English-language periodicals. The purpose of this work is to study the precedent names and analyze features of their functioning in the newspaper headlines. The study material includes Questia Online Library, where the newspaper headlines with precedent names extracted from The New Dictionary of Cultural Literacy were investigated (350 precedent names that were used in 12189 newspaper headlines). In order to achieve the purpose of the work a comparative analysis of precedent names was conducted within three cultural spheres ("Bible", "Literature", "Mythology") and discourses in American and British periodicals (37 American and 27 British newspapers). A descriptive method, a comparative method and a method of quantitative calculations were used. Having substantiated the concept of precedent names and studying their features and functions, it was proved that they are known mainly to representatives of a certain linguocultural community, and some background knowledge is needed to understand them. In order to study precedent names, their quantitative distributions by cultural spheres, years and discourses were made. The study found that the group "Literature" is one of the most productive sources of precedent names. It was proved that in the headlines for 2015-2019 the most common precedent names are the names of the cultural sphere "Literature", and the least common - "Mythology". In addition, it was determined what precedent names are the most popular in English newspaper headlines and which ones are not often used.
Keywords: прецедентний феномен; прецедентне висловлювання; прецедентний текст; лінгвокультурна спільнота